2015
DOI: 10.1186/s12879-015-1042-5
|View full text |Cite
|
Sign up to set email alerts
|

Serotype distribution and antibiotic resistance of Streptococcus pneumoniae isolates collected at a Chinese hospital from 2011 to 2013

Abstract: BackgroundStreptococcus pneumoniae infections are a major cause of global morbidity and mortality, and the emergence of antibiotic-resistant Streptococcus pneumoniae strains has been increasingly reported. This study provides up-to-date information on bacterial serotype distribution and drug resistance from S. pneumoniae clinical isolates that could guide prevention and treatment strategies for pneumococcal disease in China.MethodsA total of 94 S. pneumoniae isolates were collected from outpatients and inpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
(56 reference statements)
7
13
2
Order By: Relevance
“…Concerning the macrolides, the overall erythromycin resistance rate was 71.4%. This rate is similar to that reported in a previous Tunisian study on pneumococcal infections (64.7%), but lower than the rate reported in Chinese studies (Charfi et al, 2012;Huang et al, 2015;Pan et al, 2015). Europe and the USA have reported prevalence rates of approximately 30% .…”
Section: Discussionsupporting
confidence: 88%
“…Concerning the macrolides, the overall erythromycin resistance rate was 71.4%. This rate is similar to that reported in a previous Tunisian study on pneumococcal infections (64.7%), but lower than the rate reported in Chinese studies (Charfi et al, 2012;Huang et al, 2015;Pan et al, 2015). Europe and the USA have reported prevalence rates of approximately 30% .…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported that patterns of change in serotype distribution varies among countries and regions (Hecini-Hannachi et al, 2014;Huang et al, 2015). Serotype 14 has been described as one of the most common serotype causing invasive pneumococcal disease in children less than five years old children (Imöhl et al, 2010, Hecini-Hannachi et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Current study exhibited high resistance of Ofloxacin in adults but only 1.1 % of Ofloxacin-non-susceptible isolates are reported, although the rate of Fluoroquinolone resistance is low in this region [28]. Development of resistance to Fluoroquinolones is due to the mutations of gyrA and parC genes that further encode type II topoisomerase subunits also called quinolone-resistance determining regions [29]. Clindamycin resistance plus macrolide resistance is a suitable indicator for detection of the erm (B) resistance marker [24].…”
Section: Discussionmentioning
confidence: 99%